Electrochemical sensing of nitrate ions at Cu-immobilized gold electrode in neutral medium - Abir, Abrar Yasir; Ishmam Ibnul Arabi,; Mousumi, Nusrat Jahan; Alam, Mohammad Shariful; Ahmad, Md Faruak; Hasnat, Mohammad Abul (GUB Journal of Science and Engineering, 2024)
The Cu-immobilized Au surface was electro-catalytically employed for nitrate ions reduction in a neutral solution. According to cyclic voltammetric studies, the Cu/Au electrode has an improved electro-catalytic impact on converting nitrate ions into nitrite ions, governed by a two-electron transfer system. This modified electrode demonstrated good performance in real sample analysis along with good sensitivity (3.2518 $ μ A μ M^{-1} cm^{-2}$), long linear detection range (1.2 to 111.4 $μ M$), a very lower limit of detection (0.85 $μ M$), an excellent reproducibility. Thus, to determine nitrate ions in an aqueous media, an electrochemical sensor based on a Cu/Au electrode is suggested. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 10(1), 2023 P 75-85